Bi-allelic TTC5 variants cause delayed developmental milestones and intellectual disability. Issue 4 (21st May 2020) - Rasheed, Arisha; Gumus, Evren; Zaki, Maha; Johnson, Katherine; Manzoor, Humera; LaForce, Geneva; Ross, Danica; McEvoy-Venneri, Jennifer; Stanley, Valentina; Lee, Sangmoon; Virani, Abbir; Ben-Omran, Tawfeg; et al.
Abstract : Background: Intellectual disability syndromes (IDSs) with or without developmental delays affect up to 3% of the world population. We sought to clinically and genetically characterise a novel IDS segregating in five unrelated consanguineous families. Methods: Clinical analyses were performed for eight patients with intellectual disability (ID). Whole-exome sequencing for selected participants followed by Sanger sequencing for all available family members was completed. Identity-by-descent (IBD) mapping was carried out for patients in two Egyptian families harbouring an identical variant. RNA was extracted from blood cells of Turkish participants, followed by cDNA synthesis and real-time PCR for TTC5 . Results: Phenotype comparisons of patients revealed shared clinical features of moderate-to-severe ID, corpus callosum agenesis, mild ventriculomegaly, simplified gyral pattern, cerebral atrophy, delayed motor and verbal milestones and hypotonia, presenting with an IDS. Four novel homozygous variants in TTC5 : c.629A>G;p.(Tyr210Cys), c.692C>T;p.(Ala231Val), c.787C>T;p.(Arg263Ter) and c.1883C>T;p.(Arg395Ter) were identified in the eight patients from participating families. IBD mapping revealed that c.787C>T;p.(Arg263Ter) is a founder variant in Egypt. Missense variants c.629A>G;p.(Tyr210Cys) and c.692C>T;p.(Ala231Val) disrupt highly conserved residues of TTC5 within the fifth and sixth tetratricopeptide repeat motifs which are required for p300 interaction, while the nonsense variants are predicted to decrease TTC5 expression. Functional analysis of variant c.1883C>T;p.(Arg395Ter) showed reduced TTC5 transcript levels in accordance with nonsense-mediated decay. Conclusion: Combining our clinical and molecular data with a recent case report, we identify the core and variable clinical features associated with TTC5 loss-of-function variants and reveal the requirement for TTC5 in human brain development and health.